Elk Calf Survival and Mortality Following Wolf Restoration to Yellowstone National Park - Barber-Meyer, Shannon M.; Mech, L. David; White, P. J. (DigitalCommons@University of Nebraska - Lincoln, 2008)
We conducted a 3-year study (May 2003–Apr 2006) of mortality of northern Yellowstone elk (Cervus elaphus) calves to determine the cause for the recruitment decline (i.e., 33 calves to 13 calves/100 adult F) following the restoration of wolves (Canis lupus). We captured, fit with radiotransmitters, and evaluated blood characteristics and disease antibody seroprevalence in 151 calves ≤6 days old (68M:83F). Concentrations (x, SE) of potential condition indicators were as follows: thyroxine (T4; 13.8 μg/dL, 0.43), serum urea nitrogen (SUN; 17.4 mg/dL, 0.57), γ-glutamyltransferase (GGT; 66.4 IU/L, 4.36), gamma globulins (GG; 1.5 g/dL, 0.07), and insulin-like growth factor-1 (IGF-1; 253.6 ng/mL, 9.59). Seroprevalences were as follows: brucellosis (Brucella abortus; 3%), bovine-respiratory syncytial virus (3%), bovine-viral-diarrhea virus type 1 (25%), infectious-bovine rhinotracheitis (58%), and bovine parainfluenza-3 (32%). Serum urea nitrogen, GGT, GG, and IGF-1 varied with year; T4, SUN, and GG varied with age (P ≤ 0.01); and SUN varied by capture area (P=0.02). Annual survival was 0.22 (SE=0.035, n=149) and varied by calving area but not year. Neonates captured in the Stephens Creek/Mammoth area of Yellowstone National Park, USA, had annual survival rates >3x higher (0.54) than those captured in the Lamar Valley area (0.17), likely due to the higher predator density in Lamar Valley. Summer survival (20 weeks after radiotagging) was 0.29 (SE=0.05, n=116), and calving area, absolute deviation from median birth date, and GG were important predictors of summer survival. Survival during winter (Nov–Apr) was 0.90 (SE=0.05, n=42), and it did not vary by calving area or year. Sixty-nine percent (n=104) of calves died within the first year of life, 24% (n=36) survived their first year, and 7% (n=11) had unknown fates. Grizzly bears (Ursus arctos) and black bears (Ursus americanus) accounted for 58–60% (n = 60–62) of deaths, and wolves accounted for 14–17% (n = 15–18). Summer predation (95% of summer deaths) increased, ...